The Correlation Between Verses as I’jāz al-Qur’ān in Surah-Based Exegesis: A Study of Niẓām and Munasabah - Fachruli Isra Rukmana; Sri Kurniati Yuzar (Institut Agama Islam Negeri (IAIN) Keiri, 2023)
The interconnectedness of verses and chapters in the Quran is an intriguing method to be studied in contemporary times. Understanding the interpretation of the Quran is continually promoted by mufassīr from era to era, making Quranic exegesis a continuously evolving product. However, the explanation of the correlation between verses and chapters in the Quran has not received primary attention from scholars. This paper elucidates the concepts of munasabah and niẓām, the differences between them, the factors underlying the emergence of surah-based Quranic exegesis, and attempts to provide examples of interpretations based on the concept of correlation between verses and chapters in the exegesis of Niẓām al-Qur’ān wa Ta’wil al-Furqān bil Furqān. This research includes a literature study (library research). Specifically, the primary data in this study refers to the book Niẓām al-Qur’ān wa Ta’wil al-Furqān bil Furqān. In this article, three issues are addressed: first, what is the focal point of the differences between munasabah and niẓām in the Quran; second, what underlies the emergence of thematic exegesis based on surahs; third, how are munasabah and niẓām implemented in the Quranic interpretation applied by al-Farāhī. This article demonstrates that Al-Farāhī's exegesis book is a reference that should be developed in this era in discussing the concepts of munāsabah and niẓām in Quranic interpretation. Considering the limited attention given by Quranic scholars to interpreting the Quran with the concepts of munāsabah and niẓām, this step becomes possible to encourage once again.